Production of Volatile Organic Compounds Using Oil Palm Frond Juice as a Sole Substrate by Ceratocystis fimbriata - Nang Nor Azimah, Long Nadzri; Mior Ahmad Khushairi, Mohd Zahari; Saiful Nizam, Tajuddin; Che Mohd Aizal, Che Mohd (Penerbit UTM Press, 2017)
In this paper, the potential of oil palm frond (OPF) juice as an alternative and renewable carbon source to replace the function of glucose for the production of volatile compounds by Ceratocystis fimbriate will be reported. The OPF juice was extracted using simple physical separation method. The growths of fungi were monitored by using cell dry weight (CDW) method whereby the characterization of sugar composition and consumption of the OPF juice by Ceratocystis fimbriata were carried out using High Performance Liquid Chromatography (HPLC). The volatile organic compounds were separated and analyzed by Gas Chromatography-Mass Spectroscopy (GC-MS) with Solid Phase Micro Extraction (SPME). On the fourth day, the biomass produced by Ceratocystis fimbriata increased significantly and produced the highest number of products comprising of, 3 alcohols, 2 esters, 1 aldehyde, 1 fatty acid, 1 phenol and 1 ketone. Based on the GC-MS analysis, several volatile compounds such as aldehydes, alcohols, ketones, and esters could be produced from OPF juice supplemented with a mineral salt medium. This result shows the potential usage of OPF juice as substrates for the growth and production of volatile organic compounds by Ceratocystis fimbriata.